DROPOUTS RATES IN RELIGIOUS EDUCATION IN MUZARABANI DISTRICT SECONDARY SCHOOLS IN MASHONALAND CENTRAL PROVINCE OF ZIMBABWE - KASOWE, RITTAH (IJRDO- Journal of Educational Research, 2017)
This present study’s aim was to examine the causes of dropouts of secondary school pupils inReligious Education in Muzarabani District. A random sample of 75 teachers was used. Thedescriptive survey design was used. The questionnaire was the sole instrument used to gatherdata. The study revealed that lack of resources, culture conflicts, pupils’ attitudes,methodological problems among other factors, contributed significantly towards high dropoutrates in the subject. The study recommends that teachers should use the eclectic, multi-faithapproaches when teaching Religious education. The study also recommends that the school andthe home should play complementary roles in order to reduce cases of students dropping out ofthe subject.